FAKTOR - FAKTOR DETERMINAN TRANSFORMASI RUMAH DI BALI - Putu Sueca, Ngakan (Jurnal Natah; Vol. 3, No. 2 Agustus 2005)
In order to provide adequate housing, considerable proportion of people in the developing world transform their houses. This informal housing supply is also accurring in Bali either in most public housing or in the traditional houses. The objective of this study is to know what determinant factors of housing transformation. In order to achieve this objective, this research uses cross-sectional sample survey strategy, and two case studies were chosen. Using a questionnaire as the main vehicle, one hundred and sixty six respondents were interviewed. Regresión análysis suggests that both household and dwelling characteristics are important determinants in the decisión to transform or not. Two variables of dwelling characteristics, original house size and the original number of bedrooms, are good predictors. The research suggests that four household characteristics appear to be important, those being total expenditure, number of occupants, household type and ownership.
Keywords: determinant, housing transformation